KKN-TEMATIK PEMBERDAYAAN MASYARAKAT DESAPOLITAN JIMBUNG JOMBORAN DAN KRAKITAN ERA PANDEMI COVID-19 DI KABUPATEN KLATEN - Arif Julianto Sri Nugroho; M Puji Darmo; Endang Eko DS; Sukasih Ratna W; Gunawan Budi S; Abdul Haris; Agung Nugroho Jati; Tasari Tasari (Buletin Abdi Masyarakat, 2022)
The empowerement of village potential is one way to improve the economy.The activity of KKNT PPM in Covid-19 pandemic era in Desapolitan Jimbung Jomboran and krakitan Klaten aims to improve the empowerement people in three vilages. The models which is done include 1) entrepreneurship capacity Building and 2) Technology and Literacy Knowledge. From those activities there is a positive result which is obtained where the society, people were enthusiatic in joining program and it is led to formation of foundation for empowering people and entrepreneurship Desapolitan in the new normal after Covid-19 pandemic